The development of a quality e-learning environment based on human, social, and cultural factors - Andreou, Andreas S.; Papanikolaou, Katerina; Mavromoustakos, Stephanos; Leonidou, Constantinos (My University, 2004)
A methodology called MATHISI, for developing a quality e-learning environment based on human, social and cultural factors is presented. The three axons on which it is based are the country characteristics in which it will be implemented, the user requirements, and the application domain axon. MATHISI follows a quality development approach based on the general software quality standards as defined by the ISO 9126 and the Web engineering guidelines. The methodology incorporates learning processes and templates for developing a dynamic e-learning environment, a requirements analyzer tool to identify new user requirements and several other features.
Keywords: e-learning | e-learning environment | Methodology | Quality factors